Penggunaan Media Visual untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS Siswa Kelas V SD Inpres Tumpu Jaya I - I Ketut Selamet (Jurnal Paedagogy, 2020)
This research is motivated by the large number of students who consider that social studies subjects are boring and unattractive subjects, so that they can influence student learning outcomes. In this study, researchers tried to use visual media to overcome these problems because visual media is a good motivational tool and can stimulate students to pay attention to the material being explained. The research method used in this study is Classroom Action Research, which in its implementation has four stages namely, planning, action, observation, and reflection. Data collection techniques used in this study in the form of tests, observations, interviews, and field notes. The results of research using visual media went well and smoothly. This can be stated by an increase in learning outcomes in each cycle carried out. Where in the pre-test only 37.9% of students who successfully met the graduation standard, entered the criteria "Very lacking". At the end of the first cycle test, the students' grades increased, students who successfully met the graduation standard was 75%, entering the criteria of "Good". and increased again in cycle 2 which is 90.7%, included in the criteria of "Very Good".